1994
DOI: 10.1093/rheumatology/33.7.655
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Euroqol—a Generic Health Status Instrument—in Patients With Rheumatoid Arthritis

Abstract: The main aim of this pilot study was to test the 'construct' validity of Euroqol, a new generic health status instrument which consists of a questionnaire and visual analogue scale. Its ability to measure both current health status and change in health status was assessed in 55 patients with RA. The Euroqol questionnaire and visual analogue scales showed significant and clinically relevant correlations with other condition-specific instruments measuring loss of function, joint pain, joint tenderness and mood; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(119 citation statements)
references
References 0 publications
4
104
0
11
Order By: Relevance
“…To assess the global level of subjective pain in the target joint, continuous 100-mm Visual Analogue Scale (VAS) was adopted [25], while the Oxford Knee Questionnaire (OKQ) [26,27] and the 12-Item Short Form Health Survey (SF-12) [28,29] were used to assign specific scores to knee function and pain. Treatment effect on participants' quality of life was also evaluated at t0 and t4 using the European Quality of Life Questionnaire (EuroQoL; also known as EQ-5D) [30,31].…”
Section: Outcome Measurementmentioning
confidence: 99%
“…To assess the global level of subjective pain in the target joint, continuous 100-mm Visual Analogue Scale (VAS) was adopted [25], while the Oxford Knee Questionnaire (OKQ) [26,27] and the 12-Item Short Form Health Survey (SF-12) [28,29] were used to assign specific scores to knee function and pain. Treatment effect on participants' quality of life was also evaluated at t0 and t4 using the European Quality of Life Questionnaire (EuroQoL; also known as EQ-5D) [30,31].…”
Section: Outcome Measurementmentioning
confidence: 99%
“…The patients mark their estimate on the line. Studies on the EQ-5D have shown good reliability and validity (Brazier et al 1993;Hurst et al 1994Hurst et al , 1997van Agt et al 1994;Coast et al 1998;Dorman et al 1998). Some studies have however shown that the EQ-5D provide more missing data compared to other commonly used PROM's (Essink-Bot et al 1997).…”
Section: The Euroqol 5-dimensions (Eq-5d)mentioning
confidence: 99%
“…The baseline data listed below were collected by structured interview using standardized questionnaires and by physical examination. Data included the following: 1) sex, age, and level of education (college education or not); 2) history of the disease, with each item recorded as past or current (site of axial pain, sausage-like finger, NSAID responsiveness, arthritis [with the site], clinical hip involvement, enthesitis, chest pain, and extraarticular symptoms [psoriasis, uveitis, inflammatory bowel disease]); 3) past (last 6 months) and current treatments: disease-modifying antirheumatic drugs (DMARDs), NSAID use, ASAS-NSAID score (14), systemic corticosteroids, and analgesics; 4) burden of disease: Bath Ankylosing Spondylitis Global (BASG) score (15), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) (16), Ankylosing Spondylitis Disease Activity Score computed using the CRP level (ASDAS-CRP) (17,18), Bath Ankylosing Spondylitis Functional Index (BASFI) (19), the mental and physical dimensions of the Short Form 36-item health survey (SF-36) (20), Health Assessment Questionnaire for Ankylosing Spondylitis (HAQ-AS) (21), Ankylosing Spondylitis Quality of Life (ASQoL) score (22), and work days missed because of IBP; 5) clinical features: Ritchie articular index, synovitis index, enthesitis index, Schöber's index, chest expansion, lateral spinal flexion, cervical rotation, and physician assessment of global disease activity (PGA); 6) tobacco and alcohol use (yes/no); 7) laboratory parameters: HLA-B27 status and ultrasensitive CRP; and 8) findings from radiographs, MRI, and ultrasonography: radiographic sacroiliitis, radiographic hip abnormalities, modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) (23), MRI inflammation of the SI joints and/or spine, and power Doppler ultrasonography (PDUS) of the heel. The radiographs and MRI scans were evaluated by the local radiologist or rheumatologist using a written protocol.…”
Section: Significance and Innovationsmentioning
confidence: 99%